An overview of cord blood stem cell transplantation in Hong Kong - Leung, Chi-Kwan (Journal of Medical Science, 2022)
Haematopoietic stem cell graft derived from cord blood is standard therapy for several haematological malignancies and other diseases. The study reports cases of public and private (family) cord blood biobanking services and the related hematopoietic stem cell transplantation ever performed in Hong Kong. The published original research papers and review articles from inception to Nov 2022 have been searched for on Pubmed, Microsoft Academic Search, and Google Scholar to identify reports on existing or terminated cord blood biobanking and transplantation service in Hong Kong. Moreover, all data publicly available on the official websites of the local cord blood banks and local mainstream media has been analysed. The public Hong Kong Red Cross Blood Transfusion Service delivers the highest quantity of haematopoietic stem cell transplants. Among the private sector, HealthBaby releases the most cord blood units for clinical use in diseases in both autologous and allogeneic administration, followed by Cordlife HK.  Both public and private (family) cord blood biobanks have been and continue to contribute to the Hong Kong cord blood donor registry. However, the growth of the cord blood inventory is detrimental to donor-recipient matching for lifesaving therapy.